OC-021 Should the Renal Tract be Routinely Investigated in Iron Deficiency Anaemia?. (17th August 2016) - Lau, MS; Schembri, J; Sanders, DS; Hebden, JM
Abstract : Introduction: Iron deficiency anaemia (IDA) accounts for 4–13% of referrals to gastroenterology. The British Society of Gastronterology IDA guidelines recommend the investigation of the gastrointestinal (GI) tract, but not the renal tract. A single consultant led one stop IDA clinic was set up. As part of the evaluation of IDA, urine microscopy and an ultrasound or CT abdomen/pelvis (if used in lower GI tract examination) were performed to investigate for renal tract malignancies, alongside GI tract investigations. We aimed to demonstrate the yield of renal and GI tract malignancies in patients with IDA. Methods: Patients with IDA or isolated hypoferritinaemia attending the clinic from 2013–2015 who underwent urine microscopy and an ultrasound or CT abdomen/pelvis alongside bidirectional GI investigations (Upper GI: gastroscopy/barium swallow/CT; lower GI: colonoscopy/barium enema/CT) were analysed. We described the yield of haematuria from urine microscopy and the yield of malignancy from renal and GI tract investigations. Results: A total of 196 patients had renal tract investigations alongside bidirectional GI investigations (152 urinalysis/ultrasound, 44 urinalysis/CT). 6.1% (12/196) patients had microscopic haematuria. Four renal tract cancers were found: 2 from the haematuria group and 2 from the normal urine microscopy group. In the haematuria group, 2 bladder cancers were identified by CT and cystoscopy respectively. The latter patient was asymptomatic apart from gastroesophageal reflux and had no weight loss. He had a normal gastroscopy, colonoscopy and ultrasound abdomen. A cystoscopy was performed due to the persistent haematuria, which revealed a bladder cancer. In the normal urinalysis group, CT identified 1 prostate cancer and 1 renal cell carcinoma (RCC) where both patients presented with weight loss. The yield of renal tract malignancies in this cohort was 2.0% (4/196). The yield of GI malignancy was 3.1% (6/196) from bidirectional GI investigations in the same cohort of patients. All GI malignancies identified were colorectal cancers. Conclusion: The ratio of renal: GI tract malignancies was 2:3 in this cohort. Urine microscopy identified 50% of renal tract cancers. Following the standard practice of bidirectional GI investigations for IDA, the 1 case of asymptomatic bladder cancer would have been missed had urine microscopy not been performed. Routine urine microscopy is easy and cheap to perform, and should be tested in all patients with IDA, and those with haematuria should have their renal tracts investigated. Routine renal tract ultrasound in the asymptomatic IDA patient is not indicated. Disclosure of Interest: None Declared